Identification of the fungic microbiota isolated in areas considered aseptic - Almeida, Maria Elisabete Sbrogio de; Martini, Maria Helena; Porto, Edward; Camargo, Ana Maria Martins de; Rizzo, Edda de; Lacaz, Carlos da Silva (Revista de Saúde Pública, 1988)
The isolation and identification of the fungic microbiota present in areas considered aseptic (open and/or restricted, with or without air filtration (HEPA filters) where production of immunobiologicals is carried out)were investigated Three exposures were made with appropriate culture media, in different seasons of the year, before and immediately after the performance of the technical work. Agar-Sabouraud and agar-soy media supplemented with 0.2% yeast extract and without chloranphenicol had their efficacy tests in isolating the filamentous fungia e (molds) and yeasts in the light of the number of cultures grown and the frequency exhibited by the various specimens isolated. Sixty-seven specimens (64 of filamentous fungiae (molds) and three yeasts) have been identified. Of the filamentous fungiae (molds), 54 belonged to 22 genera of the division Deuteromycota, families Moniliaceae and Dematiaceae, five were included in the order Agonomycetales (Mycelia Sterilia), and one was classified in the order Sphaeropsidales, class Coelomycetes. Of the division Zygomycota, order Mucorales, family Mucoraceae, only one specimen could be identified as to genus. The three yeasts, belonging also to the division Deuteromycota (Fungi Imperfecti), family Cryptococcaceae, were identified as two Rhodotorula rubra and one Torulopsis candida. It was demonstrated that the number of colonies isolated in the areas studied increased after the performance of technical maneuvers and that air filtration by means of HEPA filters, reducing to number of colonies isolated in restricted areas, increased safety and is consequently recommended for working areas where successful or unsuccessful results depend on a low incidence of contamination.